Crack propagation simulation of rock-like specimen using strain criterion. (31st August 2018) - Zhao, Cheng; Ma, Chuangchuang; Zhao, Chunfeng; Du, Shigui; Bao, Chong
Abstract: A digital image correlation (DIC) method was used to obtain the full-field strain and crack propagation path for a rock-like specimen with a single prefabricated crack under uniaxial compression. Additionally, scanning electron microscopy (SEM) was used to scan the fracture surface of the specimen after compression. The macro-mechanical response of the loading process was found to be in accordance with the micro-mechanism obtained by SEM, which demonstrates that the DIC system is accurate and that the full-field strain is accordant with crack propagation. Thereafter, a strain criterion was proposed and was applied to the extending discrete element method to simulate crack propagation. The strain criterion was found to be appropriate for simulating the crack initiation stress, peak strength and crack growth morphology of the specimen. Moreover, both the numerical simulation and experimental results show that the specimen failure process had four typical stages – initiation, unstable propagation, stable propagation and failure.